Implementasi Media Augmented Reality Book Pada Materi Rantai Makanan Sekolah Dasar - Azizah, Lutfiyah Nur; Nuruddin, Muhammad (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The learning process at SDN Bandung I Diwek Jombang still uses conventional methods with lectures so that students feel bored and less active when learning takes place. In learning IPAS food chain material, 80% of the material presented is still abstract so that students can only see the pictures given by the teacher in the textbook. Leaning from this, new innovations are needed to improve student understanding and attract students to be more active in learning. The development of Augmented Reality Book media carried out using the Reserch and Development method with the ADDIE model is considered appropriate. There are 5 stages in the development process 1) Analysis 2) Design 3) Development 4) Implemtation 5) Evaluation. Based on the results of data during the research 1) The process during the development reported through field notes 2) Augmented Reality Book media developed is declared very valid to be used based on validation from media and material experts with an average of 94.5% so it is very feasible to use in the learning process of IPAS food chain material 3) Augmented Reality Book media is very interesting and feasible to use in learning food chain material based on the results of student response questionnaires with small-scale trials getting a percentage of 94% and large-scale trials with a percentage of 94.9% with an average of 94.5%. While the teacher response questionnaire obtained a percentage of 98.3%. This means that learning by using Augmented Reality Book media is very helpful in the learning process by getting positive results in its implementation.